Language Style in Digital Communication Interactions at Advertising Agencies - Huwaidah, Fatimah; Heriyati, Nungki (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This study aims to analyze linguistic phenomena in digital communication conducted by advertising agencies, particularly in their interactions with influencers as strategic partners. The research focuses on hybrid language styles, code-switching practices, and personalization strategies in shaping communication that is both effective and professional, yet friendly. A qualitative descriptive method was employed, with data collected through in-depth interviews involving 13 influencers and 3 agency representatives (Maleo, VML, and Kanan Kiri). The data were analyzed using thematic analysis to identify linguistic patterns and the pragmatic functions of commonly used phrases in digital interactions. The findings reveal that the language style adopted by advertising agencies reflects an adaptation to the digital communication landscape, where phrases like "done," "well noted," and "is it possible?" characterize a hybrid form that blends casual and formal tones. English expressions such as "thank you for reaching out" and "as per our discussion" serve to enhance the agency’s professional image, while Indonesian elements foster emotional closeness with communication partners. Moreover, hierarchical structures remain respected even within casual language use, as illustrated by phrases like “escalate to the superior”. Efficient and well-structured communication is key to ensuring smooth project execution and accelerating workflows. The study concludes that digital communication in advertising agencies serves not only as a message delivery tool but also as a strategic medium for building productive and harmonious professional relationships. These findings contribute to the development of corporate communication strategies grounded in pragmatic linguistics in the digital era. Keywords: Digital communication, Hybrid language style, Code-switching